2019
DOI: 10.1093/icvts/ivz285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aortic remodelling after conservative treatment or thoracic endovascular repair in type B dissections

Abstract: OBJECTIVES Our aim was to compare aortic remodelling in type B dissections after thoracic endovascular aortic repair (TEVAR) or conservative treatment. METHODS We conducted a retrospective analysis of computed tomography (CT) data sets at dissection onset and at the last follow-up in a group with conservative (group A) and TEVAR treatment (group B). An additional analysis of the preoperative CT images was performed in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…However, according to our study, we think there is controversy in performing TEVAR for uncomplicated ABAD with small aortic diameter only because of the rapid increase in aortic diameter in the short-term follow-up (even for patients exceeding 0.5 cm at 6 months), and further investigation is needed. Similar to our argument, a recent study has revealed that after conversion to TEVAR in conservatively pretreated chronic type B dissections, a more pronounced decrease in the diameter of the descending aorta than in patients treated in the acute phase is observed [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, according to our study, we think there is controversy in performing TEVAR for uncomplicated ABAD with small aortic diameter only because of the rapid increase in aortic diameter in the short-term follow-up (even for patients exceeding 0.5 cm at 6 months), and further investigation is needed. Similar to our argument, a recent study has revealed that after conversion to TEVAR in conservatively pretreated chronic type B dissections, a more pronounced decrease in the diameter of the descending aorta than in patients treated in the acute phase is observed [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the aortic diameter regression after TEVAR, the IMH group showed significantly better remodeling. Our previous works described a better diameter remodeling of subacute/chronic dissections than of those treated in the acute phase, which may be an explanation due to the higher rate of subacute dissections in the IMH group ( 26 ).…”
Section: Discussionmentioning
confidence: 77%
“…While malperfusion is a problem predominantly confined to the hyperacute and acute phases (ie, up to 14 days), it has been observed that remodeling (true lumen expansion and false lumen regression) of the aorta after TEVAR occurs almost exclusively in the segment that is covered by the endograft. [15][16][17][18][19] In addition, temporal changes in the structure and compliance of the dissection membrane have an important impact on long-term success.…”
Section: Long-term Outcomes Of Acute Tbadmentioning
confidence: 99%